1989
DOI: 10.1073/pnas.86.14.5434
|View full text |Cite
|
Sign up to set email alerts
|

Activation of muscle-specific genes in pigment, nerve, fat, liver, and fibroblast cell lines by forced expression of MyoD.

Abstract: MyoD is a master regulatory gene for myogenesis. Under the control of a retroviral long terminal repeat, MyoD was expressed in a variety of differentiated cell types by using either a DNA transfection vector or a retrovirus. Expression of muscle-specific proteins was observed in chicken, human, and rat primary fibroblasts and in differentiated melanoma, neuroblastoma, liver, and adipocyte lines. The ability of MyoD to activate muscle genes in a variety of differentiated cell lines suggests that no additional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
589
0
6

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 905 publications
(611 citation statements)
references
References 31 publications
16
589
0
6
Order By: Relevance
“…ruination geae number 1, MyoDI) [1] considerable interest has been focussed on the analysis of factors which induce myogenesis and the expression of musclespecific structural genes [2]. Other proteins structurally related to MyoD also convert fibroblast (C3H 10TI/2) cells into muscle cells and were named myogenin [3,4] myf-5 [5] and Mrf-4 [6] also known as herculin [7] or myf-6 [8].…”
Section: Introductionmentioning
confidence: 99%
“…ruination geae number 1, MyoDI) [1] considerable interest has been focussed on the analysis of factors which induce myogenesis and the expression of musclespecific structural genes [2]. Other proteins structurally related to MyoD also convert fibroblast (C3H 10TI/2) cells into muscle cells and were named myogenin [3,4] myf-5 [5] and Mrf-4 [6] also known as herculin [7] or myf-6 [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, exogenous MyoD in endodermal and ectodermal cells failed to induce a full phenotypic switch (Weintraub et al 1989;Sch€ afer et al 1990). Later studies revealed that MyoD induces myogenin through cooperation with the Pbx factor, which is constitutively bound to MyoD target sites in fibroblasts prior to MyoD expression (Berkes et al 2004).…”
Section: Espinosa and Emerson 2001mentioning
confidence: 99%
“…Both MyoD and myogenin can program non-muscle cells to myogenic fate and induce differentiation in vitro through a process called myogenic conversion. 52 As discussed earlier, MyoD acts upstream of myogenin and transcriptionally activates myogenin. 8,9,13,14 We anticipated that p53 would repress endogenous myogenin transcription activated by ectopic MyoD and would not repress ectopic myogenin driven by a constitutive promoter.…”
Section: Resultsmentioning
confidence: 85%